Cell culture models of oral mucosal barriers: A review with a focus on applications, culture conditions and barrier properties. Issue 3 (3rd July 2018) - Bierbaumer, Lisa; Schwarze, Uwe Yacine; Gruber, Reinhard; Neuhaus, Winfried
ABSTRACT: Understanding the function of oral mucosal epithelial barriers is essential for a plethora of research fields such as tumor biology, inflammation and infection diseases, microbiomics, pharmacology, drug delivery, dental and biomarker research. The barrier properties are comprised by a physical, a transport and a metabolic barrier, and all these barrier components play pivotal roles in the communication between saliva and blood. The sum of all epithelia of the oral cavity and salivary glands is defined as the blood-saliva barrier. The functionality of the barrier is regulated by its microenvironment and often altered during diseases. A huge array of cell culture models have been developed to mimic specific parts of the blood-saliva barrier, but no ultimate standard in vitro models have been established. This review provides a comprehensive overview about developed in vitro models of oral mucosal barriers, their applications, various cultivation protocols and corresponding barrier properties.